SAND CRAB (Emerita sp.) MEAL AS A NOVEL FEED INGREDIENT FOR KOI CARP (Cyprinus carpio) - Sukarman, Sukarman; Murniasih, Siti; Gynanjar, Rendy; Hirnawati, Rina; Zamroni, Mochammad; Solichah, Lili; Meilisza, Nina; Aulia, Megarizka; Komala, Ratna (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2023)
Sand crab (Emerita sp.) is a marine biodiversity, but it has not been used as a fish feed ingredient. This study aimed to evaluate the nutritional value of sand crabs and to understand its effect when used as feed ingredient on the performance of Koi carp. The study was conducted in two steps, which is evaluation of the nutritional value of sand crab and its effect on fish performance. The proximate composition, amino acids, and fatty acids were measured using AOAC methods, and then the carotenoid content was determined by spectrophotometry. In the second step, the sand crab was added to fish feed at doses of 0, 5, 10, and 15 percent, and fed to koi fish for 42 days. The parameters observed were length gain (LG), weight gain (WG), and feed efficiency (FE). Nutritional data were analyzed by description and compared with fish feed ingredients from previous studies. Fish performance were analyzed by one-way ANOVA. When significant, Tukey’s significant mean test was applied. The result showed that the nutritional value of sand crab was comparable to other feed ingredients with a protein content of 37.88%, while carotenoid content was superior. The best performance of Koi carp was obtained with a dose of 15% sand crab in the diet, with LG, WG, and FE values of 0.93 ± 0.05 cm, 0.48 ± 0.06 g, and 63.50 ± 7.05 %, respectively. Based on this result, it can be concluded that sand crab has a high nutritional value and can be used up to 15% in Koi carp diet.